2013
DOI: 10.1175/jcli-d-12-00520.1
|View full text |Cite
|
Sign up to set email alerts
|

The Climate of the MIS-13 Interglacial according to HadCM3

Abstract: The climate of the Marine Isotopic Stage 13 (MIS-13) is explored in the fully coupled atmosphereocean general circulation model the Hadley Centre Coupled Model, version 3 (HadCM3). It is found that the strong insolation forcing at the time imposed a strengthened land-ocean thermal contrast, resulting in an intensified summer monsoon over Asia. The addition of land ice over North America and Eurasia results in a stationary wave feature across the Eurasian continent. This leads to a high pressure anomaly over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Future studies should include the effects of changing ice sheets and associated meltwater fluxes in shaping interglacial climates. Large Northern Hemisphere ice sheets might have played an important role for regional and global climates, especially during early Brunhes interglacials (MIS 13 and before) as suggested by, e.g., Qiuzhen Yin et al (2008) and Muri et al (2013). Model studies suggest an influence of changing land ice on the interglacial climate evolution also during late Brunhes interglacial stages, like the Holocene (Renssen et al, 2009;Marzin et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Future studies should include the effects of changing ice sheets and associated meltwater fluxes in shaping interglacial climates. Large Northern Hemisphere ice sheets might have played an important role for regional and global climates, especially during early Brunhes interglacials (MIS 13 and before) as suggested by, e.g., Qiuzhen Yin et al (2008) and Muri et al (2013). Model studies suggest an influence of changing land ice on the interglacial climate evolution also during late Brunhes interglacial stages, like the Holocene (Renssen et al, 2009;Marzin et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…A recent simulation of the MIS 13 time slice at 506 ka using the CGCM Hadley Centre Coupled Model version 3 (HadCM3) (Muri et al, 2013) can be compared to our 504 ka time slice using CCSM3. Global patterns of surface temperature anomalies (relative to PI) are remarkably similar in the two different simulations with warm anomalies over all continents (except for the northern African and South Asian monsoon regions) in boreal summer and worldwide cold anomalies during boreal winter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, they also found that a small Eurasian ice sheet reinforces additionally the EASM through a topographically induced wave train, which might explain the exceptional EASM during MIS-13. These findings have been confirmed by more complex general circulation models including an atmosphere-only model ARPEGE Muri et al, 2012) and an atmosphere-ocean coupled model HadCM3 (Muri et al, 2013). However, it is still unclear if there was any other ice sheet than Greenland in the NH during MIS-13 because some terrestrial proxies seem to indicate a relatively warm condition during this interglacial (Guo et al, 2009).…”
Section: Introductionmentioning
confidence: 63%
“…"MIS-13" insolation means the insolation at 506 ka BP. "MIS-13" SST means the simulated MIS-13 SST by Muri et al (2013) using the atmosphere-ocean coupled model HadCM3 forced by the MIS-13 insolation and greenhouse gas concentrations. "Warmer warm pool" SST is the same as "MIS-13" SST except that the SST over the IPWP is increased.…”
Section: Introductionmentioning
confidence: 99%